Parental Guidance for Instilling Independence in Worship of Early Childhood in Bungbaruh Kadur Pamekasan - Abd Rosyid; Suyadi Suyadi (JOYCED: Journal of Early Childhood Education, 2022)
Worship guidance is explanation parents, or teachers give to their children to know the relationship between humans and God. This research aims to describe the guidance of parents in instilling independence in children's worship. The method used is descriptive qualitative. The research results show that parents use various strategies, namely exemplary, habituation and advice. Parents seek these multiple strategies to instill religious independence. Some parents have not fully implemented it, so the level of maturity is not optimal. Parents should be a good mirror for them. The implication is that it is easier for children to understand if given real examples, not just advice and prohibitions. An activity will belong to the child, and the child will understand what should be done.